2021
DOI: 10.5195/jmla.2021.1047
|View full text |Cite
|
Sign up to set email alerts
|

Piloting a long-term evaluation of library data workshops

Abstract: Background: Over four years of hosting library data workshops, we conducted post-workshop evaluation of attendees’ satisfaction with the workshops but not longer-term follow-up. To best allocate library resources and most effectively serve the needs of our users, we sought to determine whether our data workshops were impactful and useful to our community. This paper describes a pilot project to evaluate the impact of data workshops at our academic health sciences library.Case Presentation: We surveyed individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We speculate that as the pandemic continued, people grew weary of spending more time in virtual meetings. LaPolla, Contaxis, and Surkis also noticed a decline in attendance for their data sciences training series and posited that many professionals were experiencing "Zoom fatigue" that limited their interest in pursuing professional development opportunities [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that as the pandemic continued, people grew weary of spending more time in virtual meetings. LaPolla, Contaxis, and Surkis also noticed a decline in attendance for their data sciences training series and posited that many professionals were experiencing "Zoom fatigue" that limited their interest in pursuing professional development opportunities [24].…”
Section: Discussionmentioning
confidence: 99%
“…LaPolla, Contaxis, and Surkis studied longer-term impacts of the data workshops they offered at NYU [9] and Deardorff interviewed 14 researchers at the University of California, San Francisco before and three months after they completed introductory programming workshops [25]. Despite the low survey response rate, LaPolla, Contaxis, and Surkis's pilot confirmed that respondents benefitted from their workshops by building data collection and analysis skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In October 2020, two of the three members of the pilot team presented "The Charts Are Off: Approaches to Ethical Decision Making in Data Visualization" to the MLA Pacific Northwest Chapter [22]. This presentation focused on ethical frameworks and ethical issues connected to statistical analysis and visualization, including issues like visualizing uncertainty in data.…”
Section: Program Developmentmentioning
confidence: 99%
“…Grand Rounds Research Reproducibility (#UtahGRRR) [ 32 ] was a weekly seminar series designed to mimic traditional medical campus grand rounds series, but with an emphasis on interdisciplinarity and local experts. We envisioned #UtahGRRR to be a space where faculty, staff, students, and members of the public could share their work on reproducibility-themed topics and bring about new partnerships and cross-disciplinary collaborations.…”
Section: Spencer S Eccles Health Sciences Library University Of Utahmentioning
confidence: 99%